Measurement and dynamic evolution of relative poverty in rural areas under the background of digitalization - Qingqing Wang; Xinsheng Pang (Forestry Economics Review)
Purpose – In the digital era, measuring rural relative poverty and exploring digitalization’s role in poverty alleviation are critical for consolidating China’s poverty-eradication achievements. Design/methodology/approach – Based on the digitalization background, this paper constructs a rural relative poverty measurement system through the A-F double critical value method, measures the dynamic evolution of rural relative poverty in China from six dimensions: economy, education, health, living environment, psychological satisfaction and digitization level, and further analyzes the impact of rural digitalization development on rural relative poverty by constructing a fixed effect model. Findings – (1) The relative poverty in rural China has been significantly alleviated; (2) the slow improvement of health poverty has become an important factor influencing the progress of rural relative poverty alleviation; (3) increased digitization has demonstrated significant efficacy in alleviating relative rural poverty, with regionally heterogeneous effects characterized by stronger impacts in western regions than eastern and central areas. Originality/value – Therefore, it is necessary to establish a multidimensional relative poverty measurement standard which is more in line with the reality of rural China. More attention should be paid to the rural relative poverty in terms of health, and digital development should be utilized to improve their health level. The digital transformation of rural regions requires prioritized reinforcement, with a spatially adaptive development strategy tailored to regional disparities. Special emphasis should be placed on enhancing digital empowerment in western rural areas to ensure its targeted efficacy in driving sustainable rural revitalization.